Biomechanical comparisons of three minimally invasive Achilles tendon percutaneous repair suture techniques. (February 2022) - Melcher, C.; Renner, C.; Piepenbrink, M.; Fischer, N.; Büttner, A.; Wegener, V.; Birkenmaier, C.; Jansson, V.; Wegener, B.
Abstract: Background: While no gold standard exists for the management of Achilles tendon ruptures, surgical repair is common in healthy and active patients. Minimally invasive repair methods have become increasingly popular, while biomechanical equivalency hasn't been proven yet. Methods: A mid-substance Achilles tendon rupture was created 6 cm proximal to the calcaneal insertion in 27 fresh-frozen cadaveric ankles. Specimens were randomly allocated to 1 of 3 repair techniques: Huttunen et al. (2014) (1) PARS Achilles Jig System, Nyyssönen et al. (2008) (2) Achilles Midsubstance SpeedBridge™, Schipper and Cohen (2017) (3) Dresdner Instrument and subsequently subjected to cyclic loading with 250 cycles each at 1 Hz with 4 different loading ranges (20–100 N, 20–200 N, 20–300 N, and 20–400 N). Findings: After 250 cycles no significant differences in elongation were observed between PARS and Dresdner Instrument( p  = 1.0). Furthermore, SpeedBridge™ repairs elongated less than either Dresdner Instrument ( p  = 0.0006) or PARS ( p  = 0.102). Main elongation (85%) occurred within the first 10 cycles with a comparable elongation in between 10 and 100 and 100–250 cycles. While all repairs withstood the first 250 cycles of cyclic loading from 20 to 100 N, only the PARS (468 ± 175) and Midsubstance SpeedBridge™ (538 ± 208) survived more cycles. Within all 3 groups suture cut out was seen to be the most common failure mechanism. Interpretation: Within all groups early repair elongation was seen. While this was least obvious within the SpeedBridge™ technique, ultimate strengths of repairs (cycles to failure) were comparable across PARS and SpeedBridge™ with a decline in the Dresdner Instrument group. Highlights: All repairs survived the first 250 cycles, while none survived all 4 loading stages. Dresdner Instrument repair completed significantly less cycles prior to failure. Suture cutout at the suture-tendon interface was the primary failure mechanism. The model presents a simplified representation of the biomechanical characteristics.